ANALISA PENGENDALIAN KUALITAS PRODUK KERAMIK LANTAI DENGAN MENGGUNAKAN METODE SIX SIGMA DI PT. PRIMARINDO ARGATILE - Muhammad Rizal Mabrur; Budiharjo Budiharjo (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2021)
Quality control is a management activity to measure the quality characteristics of existing products, compare them with specifications or requirements, and take appropriate action if there is a difference between the actual appearance and standardization. The purpose of this research is to solve the causes of defective product problems that occur with the DMAIC (Define, Measure, Analyze, Improve, Control) approach to the Six Sigma method. This study uses a qualitative approach. This study analyzes defective products using the Six Sigma method in order to minimize defective products in the kiln area. Based on the research discussion, the dominant product defect is the sample in the kiln area. It is known that there are five types of product defects that can cause defective products, namely body burst by 22%, sag by 10%, preheating crack by 4%, glaze crack by 20%, and sompel by 40%. And based on the results of calculations carried out the company is at the level of six sigma 3.36 sigma